3. OUTPATIENT MANAGEMENT OF TYPE 2 DIABETES PATIENTS AND RELATED INFLUENCING FACTORS AT MY THO CITY MEDICAL CENTER IN 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current status and analyze factors influencing outpatient management of type 2 diabetes mellitus at My Tho city Medical Center in 2025.Materials and methods: A cross-sectional mixed-methods study involving 210 medical records and 10 in-depth interviews. Data were collected from January to September, 2025. Quantitative data were analyzed using SPSS 20.0 software; qualitative data by thematic analysis.Results: 100% patients had follow-up records; 87.1% had periodic glucose testing; 94.3% received prescriptions per guidelines; 92.8% adhered to monthly visits. However, only 19% received counseling on all three lifestyle aspects; 48.6% practiced self-monitoring. Key influencing factors included staff shortages, lack of equipment, ineffective health communication, and passive patient behavior.Conclusion: While diagnosis and treatment activities were well implemented, health education and self-monitoring remain limited. Reinforcement of the workforce, investment in equipment, chronic disease management software, and patient education are essential.
Keywords: Type 2 diabetes mellitus; outpatient care; primary healthcare; health education; chronic disease.